Counterbalancing ambient interference on thermal conductivity tests for energy piles. (July 2015) - Abdelaziz, Sherif L.; Olgun, C. Guney; Martin, James R.
Highlights: Modification to thermal conductivity tests to eliminate ambient interference. Enhanced thermal conductivity testing results for Energy Piles. Simple data processing is adequate for accurate and reliable results. More reliable thermal conductivity test results are obtained. Proposed technique offers a potential for shorter thermal conductivity tests. Abstract: Thermal conductivity tests on Energy Piles suffer from ambient interference on the recorded fluid temperatures. Such interference is observed as sudden fluid temperature increases or stabilizations which require advanced data processing techniques for reliable estimates of the effective ground thermal conductivity. This paper presents a modified testing procedure to eliminate the ambient interference observed in thermal conductivity tests for short ground heat exchangers including Energy Piles. The proposed testing technique relies on counterbalancing the ambient interference when heating the circulating fluid. Supported with a full-scale field experiment on an Energy Pile, the proposed testing technique showed a successful elimination of the ambient interference and an accurate estimate of the ground thermal conductivity using the simple infinite line source (ILS) model. Further, the estimated ground thermal conductivity is independent of the number of hours included in the data processing which offers the potential to reduce the testing duration and consequently the associated testing costs.